Looted, recovered, returned : antiquities from Afghanistan : a detailed scientific and conservation record of a group of ivory and bone furniture overlays excavated at Begram, stolen from the National Museum of Afghanistan, privately acquired on behalf of Kabul, analysed and conserved at the British Museum and returned to the National Museum of Afghanistan in 2012 - Ambers, J., (Archaeopress archaeology., 2014)
The 'Begram ivories' are widely considered to be miniature masterpieces of Indian art and are one of the largest archaeological collections of ancient ivories. They were excavated at the site of Begram, in northern Afghanistan, in 1937 and 1939 and belong to a period when Afghanistan, Pakistan and northern India were united under rulers of the Kushan dynasty. This book describes their story from excavation to display and return, with individual object biographies and detailed scientific analyses and conservation treatments. It also discusses how these objects have attracted very different interpretations over the decades since their discovery, and how the new analyses shed a completely fresh light on the collection.